(2x-2)(x)=264

Simple and best practice solution for (2x-2)(x)=264 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x-2)(x)=264 equation:



(2x-2)(x)=264
We move all terms to the left:
(2x-2)(x)-(264)=0
We multiply parentheses
2x^2-2x-264=0
a = 2; b = -2; c = -264;
Δ = b2-4ac
Δ = -22-4·2·(-264)
Δ = 2116
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{2116}=46$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-2)-46}{2*2}=\frac{-44}{4} =-11 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-2)+46}{2*2}=\frac{48}{4} =12 $

See similar equations:

| 5u-25=45-u | | v/17+12=14 | | 3.1(4.8a-1)-3.9=a+1 | | 6x-9=51-4x* | | (2x-16)⁰+2x=180 | | 1*1/2-2y=1/4 | | 5+4×n=17 | | (x−8)(x+7)=0 | | X+x/3=132 | | 3x+8=2×-12 | | 9x-14=2x+19 | | 6x-1+8x+7=90 | | 24x–18+12x–3=36x–21 | | 13.50-c=26.50 | | -2.5=a-1.7 | | -13-40=7(-2n+2) | | (2x+5)(x–4)=0 | | 101/6=293/4h | | (3m/4)+3=18 | | 10-5m=2m | | -2x-14=-30 | | 17d+20=-19 | | 2x²-21x=0 | | 1/9h+8=-19 | | -48=4f | | 8=3=c | | 33+e=51 | | P=1000x(1+0.05) | | 64x-4=0 | | z/6=-7 | | x^2-0.01x+1.23=0 | | -6h=-54 |

Equations solver categories